AD HOC DATA MIGRATION FOR MAINTAINING SYSTEM AVAILABILITY DURING CYBER THREAT - SAFDAR, SOHAIL (2015)
The main objective of the research is to provide the ad hoc data migration for maintaining the system availability when the system is being attacked by a cyber threat. Once the system is attacked, the data confidentiality and integrity can no longer be sustained. If the attacking threat is detected, the system services have to be discontinued in order to avoid any further violations of data confidentiality and integrity. Hence. the end users face the denial of services until the system is recovered. Existing research in the domain of information security is heavily focused on efficient threat detection and system recovery mechanisms to reinstate the system availability once the attack is rectified. The proposed research addresses the problem of system unavailability during a cyber threat attack by retaining the confidentiality and integrity of the available data. To achieve the desired research objectives, a framework is formalized that is composed of two components.